2016
DOI: 10.1504/ijbis.2016.078022
|View full text |Cite
|
Sign up to set email alerts
|

The experience of using Moodle and Elluminate Live! as learning tools in the Hashemite University case study: computer skills course

Abstract: In Jordan, e-learning tools are used to enhance the traditional learning process in traditional class rooms. Course management systems (CMS) are being utilised by many Jordanian universities to improve the learning process. The Hashemite University exploits many e-learning tools, in particular Moodle and Elluminate Live! In this paper, we will study the experience of the Hashemite University toward Moodle and Elluminate Live! In computer skills course (CS). This study helps to highlight the importance of using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Nunes et al (2015) reported the successful adaptation of Moodle for mobile devices. In addition, Obeidallah et al (2016) reported the successful combination of Moodle and illuminate in university students' learning.…”
Section: Pre-service Teachers' Rating Of Their Experience With a Moodmentioning
confidence: 99%
“…Nunes et al (2015) reported the successful adaptation of Moodle for mobile devices. In addition, Obeidallah et al (2016) reported the successful combination of Moodle and illuminate in university students' learning.…”
Section: Pre-service Teachers' Rating Of Their Experience With a Moodmentioning
confidence: 99%